(untitled) (Revista de Investigaciones Universidad del Quindío, 2010)
Lactobacillus casei is a microorganism used as a probiotic because it generates antagonistic activity against pathogens that cause gastrointestinal disorders, due to its immunomodulatory capacity and changes in pH produced by lactic acid production. For this reason, this work has focused on evaluating the growth of the microorganism and production of lactic acid using as a substrate a byproduct of the dairy industry (whey) which is a major pollutant when it is discharge into water bodies. For this research, whey was deproteinized and enriched with different amounts of glucose. Standardization of bacterial growth curves in whey was possible, with a production of cells of 5.9 X1010 CFU/mL in 75 h, lactic acid 70.39 and 76.24 g/L in 93 h with 0% and 5 % glucose respectively. Likewise, a process of liophilyzation was standardized to preserve the Lactobacillus casei produced during this investigation. Finally, we verified the purity of the strain through the API 50CH kit.